2014
DOI: 10.1177/0192513x14561522
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Employment, Work Experiences, and Financial Well-Being of Australian Mothers Who Care for Young Children With Special Health Care Needs

Abstract: The employment and work experiences of mothers who care for young children with special health care needs is the focus of this study. It addresses a gap in the research literature, by providing an understanding of how mothers' caring role may affect employment conditions, family life, and financial well-being. Quantitative data are drawn from Growing Up in Australia: The Longitudinal Study of Australian Children. The current study employs a matched case-control methodology to compare the experiences of a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
3
7
1
1
Order By: Relevance
“…For example, many families' journeys were marked by a change in employment or the development of a health problem for the parents, which corroborates research suggesting that this group of parents is particularly at risk of experiencing such difficulties (e.g. Dillon-Wallace et al 2016, Hoefman et al 2014. In several families, variations in the support network showed a weakening of ties with family and friends (especially in the period around the diagnosis) and creation of new ties (with professionals and workers in the formal network, of course, but also with people in the associational sphere).…”
Section: Discussionsupporting
confidence: 71%
“…For example, many families' journeys were marked by a change in employment or the development of a health problem for the parents, which corroborates research suggesting that this group of parents is particularly at risk of experiencing such difficulties (e.g. Dillon-Wallace et al 2016, Hoefman et al 2014. In several families, variations in the support network showed a weakening of ties with family and friends (especially in the period around the diagnosis) and creation of new ties (with professionals and workers in the formal network, of course, but also with people in the associational sphere).…”
Section: Discussionsupporting
confidence: 71%
“…The present study identified a prevalence (52%) of female CSHCN in municipality 2, contrary to the information reported in the Brazilian literature related to the subject (12) and the result found in municipality 1. Regarding caregivers, in both places mostly the mothers were responsible for the care to the CSHCN, which corroborates the conclusions of Brazilian and international investigations (13)(14) .…”
Section: Discussionsupporting
confidence: 87%
“…Financial hardship was assessed using the Family Hardship Scale, which sums the number of positive responses to seven indicators of household hardship. To calculate the Family Hardship Scales, parent/caregivers were asked to report if they had experienced any of the following situations in the previous 12 months because they were short of money: inability to pay bills on time; unable to pay mortgage or rent on time; went without meals; were unable to heat or cool the home; pawned or sold something because needed cash; sought assistance from welfare or community organization; unable to send child to kindergarten/preschool/child care for as much time as they would like (potential score 0-7) [16]. Ethnicity was considered as a potential confounder in the analysis, but was not included in any of the final models as it did not change the coefficient of breakfast skipping by at least 10% (our criterion for including a potential confounder [17]) when included in the model.…”
Section: Covariates (Wave 3)mentioning
confidence: 99%